2014
DOI: 10.47893/ijmie.2014.1197
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effect of Machining Parameters on Surface Roughness During Machining of Hardened En24 Steel Using Coated Carbide Inserts

Abstract: In the present study, an attempt has been made to evaluate the performance of multilayer coated carbide inserts during dry turning of hardened EN24 steel (47 HRC). The effect of machining parameters (depth of cut, feed and cutting speed) on surface roughness parameters (Ra and Rz) were investigated by applying ANOVA. The experiments were planned based on Taguchi’s L27 Orthogonal array design. Results showed that surface roughness parameters (Ra and Rz) are mainly influenced by feed and cutting speed, whereas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Suresh et al 21 revealed that the settings of a small span of cutting time, low feed, low cutting depth, and elevated cutting speed were useful to lessen the machining forces and surface roughness. According to Das et al, 22 the most dominant cutting variables that affect surface roughness were feed, and speed with contributions of 60.85% and 24.60% correspondingly.…”
Section: Introductionmentioning
confidence: 99%
“…Suresh et al 21 revealed that the settings of a small span of cutting time, low feed, low cutting depth, and elevated cutting speed were useful to lessen the machining forces and surface roughness. According to Das et al, 22 the most dominant cutting variables that affect surface roughness were feed, and speed with contributions of 60.85% and 24.60% correspondingly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bridging the gap between quality and productivity is essential. Achieving optimality in machining entails minimizing wear rates while maximizing productivity (Das et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only a select few biocompatible metals and alloys can function as durable orthopedic medical implants over an extended period. Stainless steel 316L, cobalt-chromium alloy, titanium, and Ti-6Al-4 V alloy are frequently utilized as bone fixators in hip prostheses and knee, external fixators, dental implants, and orthodontic wires [1]- [4]. Stainless steel (316L) is often used in orthopedic procedures because of its strong mechanical properties, flexibility, high resistance to breaking, and cost-effectiveness [5]- [10].…”
Section: Introductionmentioning
confidence: 99%